A study on preservice English teachers' self-efficacy perceptions and tendency towards academic dishonesty - (:unkn) unknown (ELSEVIER SCIENCE BV, 2010)
This study aims to examine preservice English teachers' self-efficacy and tendency for academic dishonesty levels. A total of 239 university students participated in the study. Data were gathered by using the Teacher Efficacy Scale and Tendency towards Academic dishonesty Scale. The results revealed no meaningful difference between tendency for academic dishonesty and self-efficacy perception levels by gender or school type. Additionally, 4th year students had a higher tendency for academic dishonesty than 1st, 2nd and 3rd year students; 1st, 2nd and 3rd year students had higher self-efficacy perception levels than 4th year students; and a weak, negative and meaningful relationship was found between tendency for academic dishonesty and self-efficacy perception levels. (C) 2010 Elsevier Ltd. All rights reserved. 239
Keywords: Department of English Language Teaching; preservice English teacher; self-efficacy perception; teacher self-efficacy perception; academic dishonesty; STUDENTS